Factors associated with Contraceptive Use in a rural area in the Western Cape, South Africa - Peer, Nazia (Department of Public Health and Family Medicine, 2015)
BACKGROUND: Safe and effective contraceptive use can improve women's reproductive health. Although the contraceptive prevalence rate in South Africa is comparable to rates globally, the distribution is inequitable and marginalises poor and rural women. This study aimed at identifying factors associated with contraceptive uses in a rural area in South Africa. METHO D: Cross-sectional survey data based on face-to-face interviews with female participants between 18 to 44 years were collected for a primary FAS prevention study in rural and urban South Africa. This study examined data for rural women only. The outcome variable was Effective Contraceptive use (ECC) which included use of oral contraceptives, condoms or injectables, or having been sterilised. Independent variables included socio-demographic factors, substance use, psychosocial factors, community factors, childbearing characteristics and partner characteristics RESULTS: Women were more likely to use ECC if they reported high self-esteem (compared to low or moderate self-esteem PRR=1.53; 95% CI: 0.99-2.39 ); if they strongly or moderately agreed that their culture entitled men to children compared to those who disagreed (PRR=1.55; 95% CI: 0.95-2.52); and if they had one child or more compared to no children (PRR=2.51; 95% CI: 1.64-3.84). CONCLUSION: To promote contraceptive use in in similar rural populations, family planning programmes could focus on increasing men's approval of contraception, improving partner communication around family planning and bolstering women's confidence in their reproductive decision-making, particularly their self-esteem. There should be greater focus on nulliparous women and women between 18 and 24 years old who have th e lowest Contraceptive prevalence rate (CPR).